Disordered eating and body image issues and their associated factors among adolescents in urban secondary schools in Sarawak, Malaysia - Cheah, W.L; Helmy, Hazmi; Chang, C.T (de Gruyter, 2017)
Eating disorders are common health issues among the adolescents. The objective of this study was to determine the prevalence of eating disorders and their relationship with body mass index, body part satisfaction and perception on body weight among urban secondary school children. It was a cross-sectional study conducted in Kuching, Sarawak. Data was collected using a self-administered questionnaire that consist of the Eating Attitude Test-26 (EAT-26), perception on body part satisfaction and body weight, and anthropometric measurement. Data was entered and analysed using SPSS version 22. A total of 329 respondents participated in this study with 59% females and 60.5% Malays. There were 14.3% of the respondents overweight and obese, with higher percentage among males (19.3%). About 18.5% of the respondents were found to be at risk of eating disorders with higher prevalence among males (19.3%). More females reported to have higher prevalence of body part dissatisfaction (46.9%) and body weight (37.6%) compared to males (40%, 28.1%). The statistical results indicated there were significant associations between EAT-26 and body mass index (BMI) (p = 0.039), body part satisfaction (p = 0.004), and perception of body weight (p = 0.038). Eating disorders are becoming more prevalent amongst adolescents, particularly among males. As eating disorder are strongly associated with adolescent mental and physical health, intervention programme on their developmental challenges and issues for both males and females should be in place particularly in the school education syllabus.